Respuesta :

Answer:

a. [tex] a_n = -3(5^{n - 1}) [/tex]

b. [tex]a_n = 72(3^{1 - n})[/tex]

Step-by-step explanation:

a.

[tex] a_1 = -3 [/tex]

[tex] a_2 = -3(5^1) [/tex]

[tex] a_3 = -3(5^2) [/tex]

Notice that in each term, the exponent of the 5 is 1 less than the term number.

The general term is

[tex] a_n = -3(5^{n - 1}) [/tex]

b.

[tex] a_1 = 72 [/tex]

[tex] a_2 = 72(\dfrac{1}{3})^1 [/tex]

[tex] a_3 = 72(\dfrac{1}{3})^2 [/tex]

Notice that in each term, the exponent of the 1/3 is 1 less than the term number.

The general term is

[tex] a_n = 72(\dfrac{1}{3})^{n - 1} [/tex]

[tex] a_n = 72(\dfrac{1}{3^{n - 1}}) [/tex]

[tex] a_n = 72(3^{1 - n}) [/tex]

ACCESS MORE